1989
DOI: 10.1002/jlac.198919890286
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of 2‐and 3‐Aryl‐1,4‐benzodioxanes

Abstract: 3‐Aryl‐ and 2‐aryl‐1,4‐benzodioxane derivatives of type 4d and 5d are excellent starting compounds for the synthesis of natural flavano‐ and neolignans. The syntheses of 4d and 5d were achieved with high regioselectivity by oxidative coupling of caffeic acid ethyl ester (2h) and coniferyl alcohol (1c) in the presence of a silver salt (oxide, carbonate) and potassium hexacyanoferrate(III), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…64,65 It was revealed that the substituents on the catechol fragment (i.e. 28 in Scheme 3) have a strong effect on the regioselectivity of the reaction; electron donating substituents, like methyl as in 28, strongly favour the formation of 3-aryl products (e.g.…”
Section: Further Developments and Application Of Biomimetic Methodsmentioning
confidence: 99%
“…64,65 It was revealed that the substituents on the catechol fragment (i.e. 28 in Scheme 3) have a strong effect on the regioselectivity of the reaction; electron donating substituents, like methyl as in 28, strongly favour the formation of 3-aryl products (e.g.…”
Section: Further Developments and Application Of Biomimetic Methodsmentioning
confidence: 99%
“…The mixture was stirred at room temperature for 2 h, then saturated NH 4 Cl was added, and the mixture stirred, extracted with ethyl acetate and dried, the solvent was evaporated o and the crude product was puri®ed by¯ash chromatography using light petroleum and ethyl acetate (2)-3-Methoxybenzodioxane-4,9,9'-triol Neolignan 9.ÐA solution of 8 (30 mg) in methanol (30 ml) was hydrogenated over 10% Pd/C (5 mg) under H 2 for 40 min. Then the reaction mixture was ®ltered through silica gel and preparative TLC aorded 9 as a colorless oil, 29 mg, 97% yield; H (400 MHz, [ 2 H 6 ]acetone): 1.78 (m, 2H, H-8'), 2.58 (t, 2H, J 7.7, H-9'), 3.47 and 3.69 (dd, 1H, J 12, 4, H-9), 3.55 (t, 2H, J 6.5, H-7'), 3.85 (s, SH, OCH 3 All the spectral data were in good agreement with those reported. 2 We are grateful to the National Science Foundation of China for ®nancial support.…”
Section: Methodsmentioning
confidence: 99%
“…30 In addition, a remarkable selectivity of the dirhodium reagent has been noticed when binding to substrates with more than one heterotopic ligand sites, such as various carbonyls, aromatic iso-and heterocycles, and so forth. [90][91][92] In experiments allowing intramolecular competition, e.g., with the racemic 2,3-trans-dihydro-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-1,4-benzodioxin-6-yl]-2(E)-propenoic acid ethyl ester (53; Scheme 18), 93,94 we found that a carbonyl oxygen seems always to be the better donor as compared with ether-like oxygen functionalities, as expected. 95 Clearly, there is no complexation at the 1,4-dioxane ring moiety or the methoxy group but at the ester carbonyl (Scheme 18, top); whereas signal resolution (dispersion) is found all over the molecule.…”
Section: Ethers-chiral Recognition By Nmr Spectroscopy General Princimentioning
confidence: 99%